أثر عناصر المزيج التسويقي الخدمي على الحصة السوقية للمصارف التجارية التقليدية الخاصة العاملة في سورية - العمار رضوان; عبيده هبه (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The study aims to clarify the impact of service marketing mix elements, on the market share of the private traditional commercial banks operating in Syria during the period 2010-2017. The relationship between the market share as a dependent variable and the following independent variables were studied: banking services, traditional services price, price of modern services, distribution, promotion, pepole, process, physical evidence and bank size. The study employed the methods of Panel Data through estimating Pooled Regression and Fixed Effects Models. The study concluded that there is a significant positive relation between the price of modern services, the distribution and size of the bank on the market share of the studied banks, and the existence of a significant negative relation between the process and the physical evidence and the market share of the studied banks. The study also found that there is no statistically significant relation between the number of services, the price of traditional services, promotion and pepole, and the market share of the studied banks. تهدف الدراسة إلى إيضاح أثر عناصر المزيج التسويقي الخدمي، على الحصة السوقية للمصارف التجارية التقليدية الخاصة العاملة في سورية خلال الفترة 2010) _ 2017). حيث تمت دراسة العلاقة بين الحصة السوقية كمتغير تابع وبين المتغيرات المستقلة الآتية: الخدمات المصرفية، سعر الخدمات التقليدية، سعر الخدمات الحديثة، التوزيع، الترويج، الأفراد، العملية، الدليل المادي وحجم المصرف كمتغير ضابط. تمّ استخدام أساليب تحليل بيانات السلاسل الزمنية المقطعية (Panel Data) من خلال تقدير نموذج الانحدار التجميعي (Pooled Model) ونموذج الآثار الثابتة (Fixed Effects). خلصت الدراسة إلى وجود علاقة إيجابية ذات دلالة إحصائية بين كل من سعر الخدمات الحديثة، التوزيع وحجم المصرف على الحصة السوقية للمصارف المدروسة، وإلى وجود علاقة سلبية ذات دلالة إحصائية بين كل من العملية والدليل المادي وبين الحصة السوقية للمصارف المدروسة. كما توصلت الدراسة إلى عدم وجود علاقة ذات دلالة إحصائية بين كل من عدد الخدمات، سعر الخدمات التقليدية، الترويج والأفراد وبين الحصة السوقية للمصارف المدروسة.